(3GdLhGgQ GdeVjI aj SjQI GdOhdI GdYRjIs - (3eMeO Hf UdGM GdLhgQ Hf GdMSfjs ((3eMSf Hf CMeO Hf eZd s)
(3ChdgG (B:s
(3Chd GdLRA GdChd HYO GdHSedI (B: (3CMeOc Gddge Ydi Cf habfi dUQa QjYGf GdTHGH ai EbJfGA GdYdhe hGdBOGH s
(3BNQgG (B:s
(3hBNQ GdLRA GdKGfi (B: (3hbVi dg deG bVi JGQjNg HGdNdO aEf eMeO fLd GdMSf EfJgJ GdbUjOI GdeQTjI , hde Jcf cGedI dWdH GdGNJUGQ hEdi gfG GfJgi BNQ GdcJGH GdeHGQc s
(3hGdLRA GdKGfi ef GdYbO GdefXhe ai eOM Gdehdi GdYdGeI GdPi gh Hcd NjQ eQShe s
(3hgh jJVef GdLRA GdChd ef GdOQ GdefKhQ ai SjQI Gdedc GdYGOd GdaGVd GdeTghQ eMeO Hf GdMSf Hf CejQ GdeDefjf GdefUhQ HGddgs
(3HBNQgG agQSJ hCTYGQ s
(3cJHJ GdYfhGfGJ HGdMeQI hGdUaQIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
Keywords: (3GdJGQjNs